Wild Food: Colonialism and the Construction of Australian Cuisine. Cookbooks, Cultivation and the Taste of Home - Petruso, Michaela (Culture and History: Student Research Papers, 2024)
In the intersection of food history and colonisation, historical cookbooks are often more prescriptive than representative of actual culinary habitants of individuals. In the colonial setting, cookbooks act as a marker for the subordination of indigenous cuisine in place of cuisines rooted in the heart of the empire—food becomes representative of culture, identity, and civilisation. In the Australian context, the earliest published cookbooks date back to the 1860’s, a period in which Australia saw extensive cultivation, pasteurisation, and settlement. Thus, as we trace Australian cookbooks through the late 19th and early 20th century, the inclusion and exclusion of exogenous foodstuffs becomes indicative of both colonial identity markers and performative campaigns to associate the colony with specific and particular notions of what cuisine should consist of. By analysing the recipes and discourse of historical cookbooks and emigrants’ guides in Australia, the performative nature of food asserts the tenets of culinary colonialism by maintaining spaces of control and occupation through the association of cuisine, identity, and civilisation.